A method for treatment of coloured wastewater - Idris, Azni; Abdul Razak, Putri Razreena; Hashim, Rohani; Abdul Rahman, Rakmi; Ibrahim, Zaharah; Mat Ghani, Rahani (2012)
The present invention relates to a method for treatment of coloured wastewater, characterized by the steps of conveying wastewater into a primary clarifier (110) to separate solids from liquids in the wastewater; conveying the wastewater from the primary clarifier (110) into an anaerobic reactor (130), wherein in the wastewater is circulated within the anaerobic reactor (130); collecting effluent from the anaerobic reactor (130) and conveying the effluent into an aerobic reactor (150); wherein the anaerobic reactor (130) and the aerobic reactor (150) each independently comprises a dye decolourizing bacteria mixture comprising of Enterococcus faecalis, Lysinibacillus fusiformis and Brevibacillus panacihumi in a ratio of 4:2:1; wherein the anaerobic reactor (130) and the aerobic reactor (150) each independently includes a biofilm medium for enhancing entrapment of the dye decolourizing bacteria; flowing the effluent from the aerobic reactor (150) into a secondary clarifier (170) for solids removal.